Open Problems and Conjectures on Rational Systems in Three Dimensions - Ladas, G.; Lugo, G.; Palladino, F. J. (Sarajevo Journal of Mathematics, 2024)
We present some open problems and conjectures on Rational Systems in three dimensions, or higher, with nonnegative parameters and with nonnegative initial conditions such that the denominators are always positive. We also employ the method of Full Limiting Sequences to confirm an outstanding conjecture on k^th-order rational difference equations. 2000 Mathematics Subject Classification. 39A10, 39A11